Home blood pressure monitoring (HBPM) effect on office blood pressure and medication adherence among hypertensive patients attending primary care clinic in university hospital - Jamial, Muazah Mat (2017)
Introduction: HBPM usage is increasingly popular nowadays and it is widely recommended by local and international guideline as part of the hypertensive care. Objectives: To evaluate HBPM effect on office BP and medication adherence among hypertensive patients attending primary care clinic in university hospital Methods: A randomized controlled trial was conducted from December 2014 to April 2015, involving 88 patients, allocated to either HBPM group or control group. Medication adherence was measured by a validated new Medication Adherence Score (MAS) questionnaire. Patients were seen at baseline and two months after intervention. The primary outcomes were to evaluate the differences of office BP and MAS at baseline and at two months within groups and in between groups. Results: For within group comparison, the mean changes of systolic BP (SBP), diastolic BP (DBP) and MAS were statistically significant for both groups. However, themean changes were greater seen in HBPM group than the control group (SBP 17.6mmHg, DBP 9.5mmHg, MAS 1.5 vs SBP 14.3mmHg, DBP 6.4mmHg, MAS 1.3). For comparison in-between group at two months, the adjusted mean difference for: mean SBP was 4.74 (95% CI -0.65 mmHg to 10.13 mmHg) (p=0.084); mean DBP was 1.41(95% CI -2.01 mmHg to 4.82 mmHg) (p=0.415) and mean MAS was 0.05 (95% CI -0.29 mmHg to 0.40 mmHg) (p=0.768). There were no significant differences between the two groups in all variables at 2 months of the study Conclusion: HBPM of two months results in greater reduction of office BP and improvement in medication adherence even though it is statistically no difference to usual care. Therefore, further studies with longer duration are recommended to assess the long term effect of HBPM.